2017
DOI: 10.5194/dwes-10-83-2017
|View full text |Cite
|
Sign up to set email alerts
|

Identifying (subsurface) anthropogenic heat sources that influence temperature in the drinking water distribution system

Abstract: Abstract. The water temperature in the drinking water distribution system and at customers' taps approaches the surrounding soil temperature at a depth of 1 m. Water temperature is an important determinant of water quality. In the Netherlands drinking water is distributed without additional residual disinfectant and the temperature of drinking water at customers' taps is not allowed to exceed 25 • C. In recent decades, the urban (sub)surface has been getting more occupied by various types of infrastructures, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Measurements of soil temperatures in The Netherlands have shown that soil temperatures at depth of 1.0 m in a warmer than average summer with a heat wave can reach very local up to 27 • C and can heat up at a rate of 1 • C per day, in so-called 'hot-spot' locations. Examples of 'hot-spot' locations are industrial areas with large anthropogenic heat sources, with no vegetation and good drainage that prevents infiltration and fully exposed to the sun radiation [21].…”
Section: Drinking Water Temperature In the Transport And Distributionmentioning
confidence: 99%
See 4 more Smart Citations
“…Measurements of soil temperatures in The Netherlands have shown that soil temperatures at depth of 1.0 m in a warmer than average summer with a heat wave can reach very local up to 27 • C and can heat up at a rate of 1 • C per day, in so-called 'hot-spot' locations. Examples of 'hot-spot' locations are industrial areas with large anthropogenic heat sources, with no vegetation and good drainage that prevents infiltration and fully exposed to the sun radiation [21].…”
Section: Drinking Water Temperature In the Transport And Distributionmentioning
confidence: 99%
“…Although several soil temperature models for rural areas have been proposed, little is known about the soil temperature profile in urban areas. A one-dimensional soil temperature model was developed by Blokker and Pieterse-Quirijns [11] and extended by Agudelo-Vera et al [21] to include anthropogenic heat sources, as seen in Figure 5. Drinking water temperature in tropical countries could be even higher; nine water samples collected on different days in the city of Cali (Colombia) resulted in temperatures between 25 °C and 28 °C [24].…”
Section: Drinking Water Temperature In the Transport And Distributionmentioning
confidence: 99%
See 3 more Smart Citations